(3bUU GdCfHjGAs - (3GdcSGFj , eMeO Hf YHO Gddg GdcSGFj, CHh GdMSf CHh LYaQs ((3eMeO Hf CMeO Hf YWGa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfHJ GdNdb fHGJkG gPG cJGH EHJOGA GdeHJOC ef Ndb Gddg JYGdi deG EHJOC Ndb GdSehGJ hGdCQVjf hNdb GdLf hGdCfS hCMhGd GdfHjjf Ydjge GdSdGe s
(3BNQgG (B:s
(3hhbaJ Hjf jOi jhfS Ydjg GdSdGe acdeJg HEPf Gddg hbGdJ dg be aGTQH ef dHfi aTQH ef dHfgG aQO Gddg Ydjg bhJg hMSfg hLeGdg Je GdcJGH GdeHGQc HMeO Gddg JYGdi hYhfg hMSf Jhajbg s
(3HChdg agQS ddcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1328s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs